Left-Sided Upper Partial Anomalous Pulmonary Venous Return through a Curved Vein Joining the Left Brachiocephalic Vein - Eleonora Tricarico; Francesco Tricarico; Carlo Florio (Case Reports in Radiology)
The evaluation of pulmonary veins during cross-sectional imaging of the chest and the knowledge of their embryology and anatomy are useful for detecting congenital conditions that may be clinically significant. Moreover, with the spread of cross-sectional imaging it is very frequent to find anatomical variants; therefore the radiologist should easily recognize their appearances. This case report shows a left-side upper partial anomalous pulmonary venous return (PAPVR) through a “curved” vein that joins the left brachiocephalic vein, in a female patient who underwent whole-body computed tomography (CT) for staging endometrial cancer. This was an incidental finding, not related to any symptoms; however, we explain the anatomical aspects of this abnormality within the congenital condition of PAPVR and its possible clinical relevance.